PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2010-2014) - B51111100, Verny Salim (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
In recent years Intellectual Capital has a key in improving values in some companies. This occurs because Intellectual Capital is the foundation for the company to be more competitive. The research aimed to find out the effect of IC on company’s value and to know whether IC had different effect on banks of state-owned enterprises and banks of non state-owned enterprises. The independent variable was IC and the dependent variable was company’s value. The data was gathered from 130 Indonesian bankings taken from Indonesia Stock Exchange between 2010 and 2014. The research used Pulic Model (Value Added Intellectual Coefficient- VAICTM) as a measure of officiency for IC, Physical Capital Coefficient (VACA), Human Capital Coefficient (VAHU) and Structural Capital Coefficient (STVA). Simple linear regression analysis was used to test the influence between VAICTM and the company’s value in which financial ratios were selected as proxy measure for the value of the company and to examine whether there was different effect between VAICTM and the company’s value in banks of state-owned enterprises and banks of non state-owned enterprises. Key words: Intellectual Capital, Company’s Value, Simple Linear Regression